His-Purkinje system-related incessant ventricular tachycardia arising from the left coronary cusp - Eiji Sato, MD; Tetsuo Yagi, MD, PhD; Akio Namekawa, MD; Akihiko Ishida, MD; Yoshiaki Mibiki, MD, PhD; Yoshihiro Yamashina, MD, PhD; Hirokazu Sato, MD, PhD; Takashi Nakagawa, MD; Manjirou Sakuramoto, MD; Jyuri Komatsu, MD; Tomoyuki Yambe, MD, PhD (Journal of Arrhythmia, 2014)
We describe the case of a 23-year-old woman who had His-Purkinje system-related incessant ventricular tachycardia with a narrow QRS configuration. The ventricular tachycardia was ablated successfully in the left coronary cusp where the earliest endocardial activation had been recorded. We hypothesize that a remnant of the subaortic conducting tissue was the source of the ventricular arrhythmias.